A importância do nivelamento acadêmico nas disciplinas pré-clínicas no curso de Odontologia - RÊGO, Larissa Freitas (2023)
The entrants from Brazilian Universities have a heterogeneous origin, coming from diverse socioeconomic and educational realities. For some academics, these disparities hinder learning and generate disinterest, a fact that predisposes dependence and evasion in educational institutions. As a way to create conditions to favor the integral formation of these university students, among other measures in the institutional development plan, there is the project for a leveling of learning course that aims to serve students who have learning gaps and difficulties regarding basic contents. Based on this, the pre-clinical leveling program was created, aimed at entrants of the third semester of the Dentistry course at the Universidade Federal do Pará. This program that, through expository classes, practical and evaluative activities, provides a qualitative increase in the knowledge of fundamental contents for the understanding of the semester subjects, such as anatomy, radiology, and stomatology. The preclinical leveling was carried out with entrants from the 2019.4 and 2020.2 academic periods, the questionnaire applied at the end of the course revealed the good acceptance of the academics, since they unanimously pointed out that the program should continue. The pre-clinical leveling has a great importance, because it seeks to minimize knowledge gaps, and favors the interaction of theoretical and practical knowledge of academics, thus promoting a democratic formation of future dentists.